2022
DOI: 10.26436/hjuoz.2022.10.2.776
|View full text |Cite
|
Sign up to set email alerts
|

Ifrs Adoption and Value Relevance of Accounting Information of Listed Industrial Goods Firms in Nigeria

Abstract: The study examines the effect of IFRS adoption on the value relevance of accounting information of six (6) out of thirteen (13) listed industrial goods firms in Nigeria for the period of fourteen years (2007-2020); seven (7) years before IFRS adoption and seven (7) years after IFRS adoption. Earnings per share (EPS), Book value per share (BVPS) and Dividend per share (DPS) constitute the independent variables and share price as the dependent variable.  Ex-post facto research design was employed and multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…We therefore reject the null hypothesis. This is in line with the findings of Mamuda (2015), Omokhudu and Ibadin (2015) and Ernest and Oscar (2014). This reveals that a one-naira increase in earnings will result to 0.22-naira increase in the prices.…”
Section: Earnings Per Share and Market Share Pricessupporting
confidence: 92%
See 3 more Smart Citations
“…We therefore reject the null hypothesis. This is in line with the findings of Mamuda (2015), Omokhudu and Ibadin (2015) and Ernest and Oscar (2014). This reveals that a one-naira increase in earnings will result to 0.22-naira increase in the prices.…”
Section: Earnings Per Share and Market Share Pricessupporting
confidence: 92%
“…Additionally, Mamuda (2015) studied value relevance in the listed industrial good firms in Nigeria, between the year 2007 and 2013, with a sample size of sixteen firms out of the twenty five listed firms, using OLS technique of data analysis, the study found earnings per share, dividend per share, book value per share to be statistically and significantly correlated with market value. Despite the study reported mix findings by previous studies reviewed, however it made no effort to tackle the problem.…”
Section: Review Of Related Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, internal public debt and total revenue were taken as two independent variables (Abdullah H & Tursoy T, 2023;Ibrahim P et al, 2022;Mohammed et al, 2019).…”
Section: Research Data and Variablesmentioning
confidence: 99%